Increase Student Learning Interest in Covid-19 with Digital Teaching Materials - Kiriana, I Nyoman (Universitas Pendidikan Ganesha, 2021)
The problem behind this research was the implementation of learning courses that tend to attract less students to study. This research was research and development. The subject of the research trial was a student of the Religious Education Study Program. The data collected in this research were data from expert test subject content, design expert test, learning media expert test, and from student trials. Data collection instrument used in the form of evaluation sheet (questionnaire). Data analysis used qualitative and descriptive quantitative descriptive analysis. The results of the assessment of media products were carried out based on six aspects, namely: aspects of the content of the field of study / with a percentage of achievement rate of 87.00% with a worthy predicate; reviewed from the aspect of learning design with a percentage of achievement rate of 85.55% worthy predicate; reviewed from the aspect of learning media with a percentage of achievement rate of 88.00% worthy predicate; reviewed from the aspect of individual trials, with a percentage rate of 90.65% pedikat very feasible; small group trials, with a percentage achievement rate of 95.55% predicate is very feasible;and reviewed from the aspect of field trials with a percentage achievement rate of 94.45% predicate is very feasible. Thus this product in the form of teaching materials has a good level of validity and deserves to be used in the learning process in religious education courses.